2021
DOI: 10.1101/2021.01.23.427917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic adaption to extracellular pyruvate triggers biofilm formation inClostridioides difficile

Abstract: Clostridioides difficile infections are associated with gut microbiome dysbiosis and are the leading cause of hospital acquired diarrhoea. The infectious process is strongly influenced by the microbiota and successful infection relies on the absence of specific microbiota-produced metabolites. Deoxycholic acid (DOC) and short chain fatty acids are microbiota-produced metabolites that limit the growth of C. difficile and protect the host against this infection. In a previous study, we showed that DOC causes C. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…Moreover, we did not only confirm the importance of c-di-GMP signaling in biofilm formation but further suggested a central role for SigL/RpoN in C. difficile biofilms and conclude that research on this well-conserved regulator is hitherto underrepresented ( Table 2 ). Of note, Tremblay et al (2021) recently suggested a role for SigL/RpoN in C. difficile biofilms. Likewise, the data presented here emphasize the importance to characterize various still uncharacterized transcriptional regulators and two-component systems of which several were induced in aggregate biofilms ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not only confirm the importance of c-di-GMP signaling in biofilm formation but further suggested a central role for SigL/RpoN in C. difficile biofilms and conclude that research on this well-conserved regulator is hitherto underrepresented ( Table 2 ). Of note, Tremblay et al (2021) recently suggested a role for SigL/RpoN in C. difficile biofilms. Likewise, the data presented here emphasize the importance to characterize various still uncharacterized transcriptional regulators and two-component systems of which several were induced in aggregate biofilms ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the diversity of conditions also makes it difficult to compare studies and draw accurate conclusions. The recent development of a semi-defined medium that supports biofilm formation may help bridge those gaps in knowledge and resolve current discrepancies [ 192 ].…”
Section: Biofilm Formation In C Difficilementioning
confidence: 99%
“…The biofilm matrix is typically composed of DNA, polysaccharides, and proteins, but the composition varies according to species. For C. difficile , eDNA is an essential structural biofilm component under all conditions tested [ 184 , 192 , 201 , 204 ]. Specifically, adding DNAse I before biofilms were formed prevented their formation [ 184 , 201 ], and DNAse I dispersed pre-formed biofilms [ 184 , 204 ].…”
Section: Biofilm Formation In C Difficilementioning
confidence: 99%
See 2 more Smart Citations